2010
DOI: 10.1074/jbc.m110.114447
|View full text |Cite
|
Sign up to set email alerts
|

Wilson Disease at a Single Cell Level

Abstract: Wilson disease (WD) is a severe hepato-neurologic disorder that affects primarily children and young adults. WD is caused by mutations in ATP7B and subsequent copper overload. However, copper levels alone do not predict severity of the disease. We demonstrate that temporal and spatial distribution of copper in hepatocytes may play an important role in WD pathology. High resolution synchrotron-based x-ray fluorescence imaging in situ indicates that copper does not continuously accumulate in Atp7b ؊/؊ hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 25 publications
(19 reference statements)
3
52
0
Order By: Relevance
“…In spite of that there are genetic mechanisms that control copper metabolism and homeostasis, related to copper absorption in many of the mammalian tissues, namely in the enterocyte, controlled by Ctr1 (a plasma membrane copper transport protein) [19]. It seems that copper transporter Ctr1 is downregulated when Cu is overloaded in the hepatocytes in WD [20]. If so, the downregulation of Ctr1 expression could lead to an augmentation of intestinal Cu content and inflammatory exacerbation, but a relationship between this transporter and inflammatory bowel disease has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of that there are genetic mechanisms that control copper metabolism and homeostasis, related to copper absorption in many of the mammalian tissues, namely in the enterocyte, controlled by Ctr1 (a plasma membrane copper transport protein) [19]. It seems that copper transporter Ctr1 is downregulated when Cu is overloaded in the hepatocytes in WD [20]. If so, the downregulation of Ctr1 expression could lead to an augmentation of intestinal Cu content and inflammatory exacerbation, but a relationship between this transporter and inflammatory bowel disease has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal and spatial distribution of Cu in hepatocytes may play an important role in Wilson’s disease pathology. Using high resolution synchrotron-based x-ray fluorescence imaging in situ, Ralle et al (2010) have shown that Cu does not continuously accumulate in ATP7B(−/−) hepatocytes. The lack of further accumulation is associated with the loss of Cu transporter CTR1 from the plasma membrane and the appearance of Cu-loaded lymphocytes and extracellular Cu deposits.…”
Section: Cu Toxicitymentioning
confidence: 99%
“…108 One possible reason for this inconsistency is the abnormal distribution of copper in hepatocytes in animal models of WD. 109 It is also not clear to what degree the human WD phenotype is influenced by reduced protein levels and copper inhibition of ACHY. Betaine supplementation increases SAM and Dnmt3b levels and restores DNA methylation in the liver.…”
Section: Evidence Of Epigenetic Regulation In Wilson Diseasementioning
confidence: 99%